2012
DOI: 10.1093/geront/gns093
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life: Expanding a Conceptual Framework to Include Older Adults Who Receive Long-term Services and Supports

Abstract: For older adults receiving long-term services and supports (LTSS), health-related quality of life (HRQoL) has emerged as a critical construct to examine because of its focus on components of well-being, which are affected by progressive changes in health status, health care, and social support. HRQoL is a health-focused quality of life (QOL) concept that encompasses aspects of QOL that affect health such as function, physical, and emotional health. Examining existing theoretical constructs and indicators of HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 49 publications
4
99
0
5
Order By: Relevance
“…The framework that guided this study, reported in an earlier paper 17 , was an adaptation of the Wilson & Cleary HRQoL conceptual model. 11 Briefly, this model describes relationships between and among multiple HRQoL domains including biological and physiological factors, symptom status, physical functional status, general health perceptions, social support and overall quality of life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework that guided this study, reported in an earlier paper 17 , was an adaptation of the Wilson & Cleary HRQoL conceptual model. 11 Briefly, this model describes relationships between and among multiple HRQoL domains including biological and physiological factors, symptom status, physical functional status, general health perceptions, social support and overall quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…12,13,15,16 HRQoL is now recognized as a complex construct, encompassing multiple domains, including biological and physiological factors, symptom status, physical and cognitive functional status, general health perceptions, emotional status, social support and overall quality of life. 17 …”
Section: Introductionmentioning
confidence: 99%
“…The Donabedian framework, while useful for understanding the sequence of how a particular health care setting affects individual outcomes, does not incorporate individual characteristics as predictors of outcomes and is not specifically developed for long-term care (LTC) settings. A conceptual model developed by Zubritsky et al (2013) focuses on health-related QOL for persons in LTC. The model views QOL as multidimensional and influenced by the characteristics of both individual and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary data analysis was conducted using an extant data set from a National Institute on Aging-funded longitudinal observational cohort study entitled, Health Related Quality of Life: Elders in Long Term Care (HRQoL), R01AG025524 , hereafter referred to as the “parent study” (Naylor et al, 2016; Zubritsky et al, 2013). …”
Section: Methodsmentioning
confidence: 99%